Implementation of Problem Based Learning Model in Islamic Education Learning to Improve Student Learning Outcomes at SD Negeri 09 Tanjung Medan - Nurhabibi; Taufiq, Ahmad; Hasibuan, Maesyaroh (Jurnal Pendidikan Profesi Guru, 2023)
This study aims to Improve Student Learning Outcomes in Islamic Education Using the Problem Based Learning Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to Improve Student Learning Outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Learning using the Problem Based Learning Learning Model can Improve Student Learning Outcomes. This can be seen from the increase in the percentage of completion of the Improvement of Student Learning Outcomes in each cycle with details of the pre-cycle 47.64%, the first cycle 78.57% and in the second cycle increased to 88.57%. Thus, learning using the Application of the Problem Based Learning Learning Model can be used as an alternative to Improve learning outcomes.